ISOLATE AND DIAGNOSE CANDIDA ALBICANS FROM WOMEN WITH VULVOVAGINAL CANDIDIASIS AND ESTIMATE THE LEVELS OF SOME CYTOKINES - Hussein, Anmar Sael; Ahmad, Ghfran Ayad (PT. Antis International Publisher, 2024)
Candida albicans is the opportunistic mucosal infection that causes vulvovaginal candidiasis, which affects a lot of otherwise healthy women who are of childbearing age. So, the current study aimed to isolate and diagnose C. albicans from women with Vulvovaginal candidiasis and estimate the levels of some cytokines. Vaginal and blood samples were collected from women attending Salah al-Din Teaching Hospital, Department of Obstetrics and Gynecology - Consultation Clinic, and two groups of women were selected. The first group includes 200 women suffering from infections and their ages range from 18-59 years, and a second group of healthy women (40 women) whose ages range from 17-50 years for the period from November 2023 to May 2024. 200 samples were directly inspected under a microscope; of these, 58(29.0%) were found to be positive and 142(71.0%) to be negative. On the other hand, the Human C. albicans ELISA Kit was used for the purpose of detecting positive cases and their percentage. The results found that out of 200 women suffering from vaginitis, it was found that 27.5% were positive on the test, while the negative percentage of the test was 72.5%. for cytokines, IL-10 levels in serum of patients (37.15± 5.04) demonstrated significant (P <0.05) increase in compared with healthy subjects (14.94± 1.78). the levels of IFN-γ demonstrated significant (P <0.05) increase in patients (158.74 ± 12.55) compared with healthy subjects (39.13 ± 4.25). It is concluded that using the ELISA method is the best compared to traditional methods for diagnosing C. albicans, and vulvovaginal candidiasis led to an increase in the secretion of both IL-10 and IFN-γ for the purpose of raising the immune response